TRIP JAWA TIMUR - Firza Azzam Fadilla; Rully Putri Nirmala P; Wiwin Hartanto (LP4MK STKIP PGRI Lubuklinggau, 2019)
TRIP stands for the Army of the Republic of Indonesia Student. The emergence of the East Java TRIP, which was originally an activity spearheaded by a group of students in the Surabaya area who had an interest in Indonesian independence and had a desire to fight for independence at that time. So that the students form a student struggle organization that is often known as TRIP, the organization was formed during the era of the independence war in 1946 in the Surabaya area. together with the formation of East Java TRIP Battalions in Mojokerto, Kediri, Besuki and Malang after the East Java Student Congress was held in the city of Malang in East Java, the result of the congress was the election of mas Isman as chairman or leader of the Student People's Security Row in Surabaya Java Timur on October 25, 1945. (History, Republic, Student, Year, & Suryadi, 2018). After TRIP in East Java was formed in the Surabaya area on September 21, 1945, the student fighters formed a Battalion consisting of 5 Battalions including; Battalion 5000 at Malang Residency, 1000 Battalion in Jetis, Mojokerto area. 3000 Battalion at Kediri Residency, 4000 Battalion at Besuki Residency (Jember, Situbondo, Bondowoso, Banyuwangi) and 2000 Battalion at Madiun Residency. Looking at the events of fighting in order to maintain independence in East Java, the role of the influence of the East Java